Pengaruh Nilai Ekspor Dan Impor Migas Dan Non-Migas Terhadap Inflasi di Indonesia - Achmad Ulil Albab; Jaka Nugraha (Universitas Negeri Surabaya, 2022)
Abstract Indonesia is one of the exporting and importing countries of goods and services in the form of oil and gas and non-oil and gas. BPS, recorded data on exports and imports of oil and gas and non-oil and gas continues to increase. The increase in exports and imports of these commodities was also in line with the increase in inflation in recent months. Inflation affects the value of oil and gas and non-oil exports and imports. This study intends to analyze the influence of the value of exports and imports of oil and gas and non-oil and gas on inflation in Indonesia. The research method used is quantitative method with multiple regression analysis test analysis technique with secondary data collection through BPS. The conclusion of the study shows that oil and gas exports have no effect on inflation, non-oil and gas exports have no effect on inflation, oil and gas imports have no effect on inflation, non-oil and gas imports have no effect on inflation.